Educators' experiences of psychosocial support workshops during COVID-19 in Eastern Cape, South Africa - Mabaso, Rendani Mirriam (Rhodes University, Faculty of Humanities, Department of Psychology)
There is growing awareness of the value and central role of immediate and long-term mental health and psychosocial support (MHPSS) interventions, especially during times of crisis such as Covid-19. The World Health Organization has identified the education sector as a crucial intervention site for public mental health promotion. In collaboration with members of the Makhanda education community, the Rhodes University Community Engagement office identified psychosocial support for educators and educational practitioners as a key societal and educational challenge. Focusing specifically on the experiences of educators, this study sought to solicit their experiences of MHPSS workshops in a rural city of the Eastern Cape province of South Africa. Focus groups with educators and educational practitioners in non-government organisations, care centres and other educational settings who participated in the psychosocial support workshops were conducted. Data was analysed using community psychology's social action framework. Four broad themes emerged from the data: the responsibilisation of educators during and post-Covid-19, educators' resilience and support for each other, educators' mental health promotion through psychosocial support workshops, and top-down intervention strategies that fall short in addressing educators' and learners' needs. This study demonstrates the value of university-community partnerships in education settings which are key sites for public mental health promotion. In this study, I advocate psychosocial support as a standard practice available for educational practitioners and show how professional training programmes in higher education can be responsive to societal challenges via collaborative approaches.
Keywords: Educators Mental health -- South Africa -- Eastern Cape; Psychosocial support system; COVID-19 Pandemic, 2020-2023 Influence; Community psychology; Service learning